Diseño de un manual BPM para la panadería pastelería la corteza de la Universidad de las Américas Quito-Ecuador - Yumi Huebla, Diego Manuel (2019)
Summary this document is the result of four phases that have been developed in four chapters. The topic is Good Manufacturing Practices in the production process of La Corteza. The first chapter is the background for the development of the thesis subject, their beneficiaries and because of it is a relevant topic that should be implemented. The second chapter includes conceptual definitions that are GMP and its scope. Then the third chapter establishes the diagnosis of the current situation in La Corteza, through data collection and analysis of these. The Decree 3253 issued by the Government of the Ecuadors Gustavo Noboa, eliminating those who are not applicable in La Corteza using an array that contains all the requirements of normative reference. The fourth chapter, develop the manual in which it is based the implementation of Good Manufacturing Practices. And the documentation was elaborated for it.